The prediction of two-dimensional PbN: opened bandgap in heterostructure with CdO - Cheng, Zhang; Wang, Yuelei; Zheng, Ruxin; Mu, Weihua (Frontiers in Chemistry, 2024)
The development of two-dimensional (2D) materials has received wide attention as a generation of optoelectronics, thermoelectric, and other applications. In this study, a novel 2D material, PbN, is proposed as an elemental method using the prototype of a recent reported nitride (J. Phys. Chem. C 2023, 127, 43, 21,006–21014). Based on first-principle calculations, the PbN monolayer is investigated as stable at 900 K, and the isotropic mechanical behavior is addressed by the Young’s modulus and Poisson’s ratio at 67.4 N m–1 and 0.15, respectively. The PbN monolayer also presents excellent catalytic performance with Gibbs free energy of 0.41 eV. Zero bandgap is found for the PbN monolayer, and it can be opened at about 0.128 eV by forming a heterostructure with CdO. Furthermore, the PbN/CdO is constructed by Van der Waals interaction, while the apparent potential drop and charge transfer are investigated at the interface. The PbN/CdO heterostructure also possesses excellent light absorption properties. The results provide theoretical guidance for the design of layered functional materials.